Preparation and properties of controlled compacting filling material based on admixture technique. Issue 1 (19th February 2018) - Zhang, Xuesong; Yu, Rangang; Chen, Jinping
Abstract : Using fly ash as the main raw material with a certain amount of cement, polycarboxylate super plasticizer and the admixture such as slump retaining agent and thickening agent, a type of controlled low-strength materials is developed that can be used to fill the discarded oil pipeline. Controlled compacting filling materials exhibit good fluidity and low compressive strength. These materials can take advantage of waste efficiently. With the aid of some admixtures, such as polycarboxylic high performance water-reducing agents DW-I and DWB01 and thickening agent carboxymethyl cellulose, fly ash as a raw material is mixed with 10–15 wt% cement to prepare low-cost controlled compacting filling material that meets the fluidity and compressive strength required to fill an unused oil pipeline. Given the local elevation difference along the wasted pipeline, this material can rely on gravity transportation to fill in the terminal position of the pipeline and self-compact, which can reap economic and environmental benefits.